In-vivo blood flow parameters can predict at-risk aortic aneurysms and dissection: a comprehensive biomechanics model. (25th November 2020) - Salmasi, M; Jarral, O.A; Pirola, S; Sasidharan, S; Pepper, J; Oo, A; Moore Jr, J; Xu, X.Y; Athanasiou, T
Abstract: Background: Abnormal blood flow patterns can alter the material properties of the thoracic aorta via altered vascular biology and tissue biomechanics. In-vivo haemodynamic assessment of the aorta is yet to penetrate clinical practice due to our limited understanding of its effect on aortic wall properties. The decision for surgical treatment is based on size thresholds, limited to a single measurement of aortic diameter from routine imaging, although many aortic dissections (40–60%) occur below these size thresholds. This multi-centre study aims to assess the clinical utility of biomechanics principles in thoracic aortic aneurysm (TAA) risk rupture prediction using a substantial sample size. Methods: Fifty-five patients undergoing surgery for root or ascending TAA were recruited from five cardiac centres. Bicuspid aortic valves and connective tissue disease were excluded from this study.Haemodynamic assessment Pre-operative 4-dimensional flow magnetic resonance imaging (4D-MRI) were conducted. Direct 4D-flow analysis and computational fluid dynamics (CFD) were performed creating detailed wall shear stress (WSS) maps across the whole aneurysms. Aortic wall assessment The aneurysmal aortic sample was obtained from surgery and subjected to region specific uniaxial failure tests in the circumferential and longitudinal directions, as well as delamination testing within the aortic media. Whole aneurysm histological characterisation was also conducted using computational pathology techniques. Blood flow, tissue mechanics and microstructural properties were used to develop a risk prediction model with assessment of elastin, collagen and smooth muscle cell composition, as well as failure strain assessment and dissection energy function. Results: Outcomes of mechanical properties were: Young's Elastic Modulus as a measure of aortic stiffness (0.85 MPa ±0.69), as well as maximal tensile strength (0.49 MPa ± 0.36), which demonstrated reduced aortic wall strength in the outer curvature. This correlated with increased wall shear stress (WSS) (up to 10 Pa) and flow velocity (up to 43 l/min). Regions of abnormal flow and tissue mechanics correlated significantly with degraded medial microstructure (elastin abundance: 34 vs 66%; collagen abundance 26 vs 57%, p<0.05). Conclusions: CFD modelling has the potential to provide a risk prediction of acute events in TAA beyond the current size classification, as validated by altered aortic tissue properties. Future longitudinal studies are warranted to validate this methods in moderately enlarging thoracic aortas. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): NIHR Imperial College BRC